Tautan Politik Antara AAM Dengan Konstituen di Dapil Tulungagung II dalam Pemenangan Pileg Kabupaten Tulungagung Tahun 2019 - David Kamaluddin El Barito; Ahmad Zaki Fadlur Rohman (Universitas Warmadewa, 2023)
In the open proportional legislative election system, the relationship between the legislative candidates and their constituents is the primary factor that determines their electability in parliamentary seats. Especially in areas with a high population, it causes hard efforts for a legislative candidate to spread his influence in society, even though in unconstitutional ways. As a result, the pathology of democracy will slowly emerge and undermine the existing political system. Therefore, the model of the legislative candidate's approach to constituents is considered to be an important thing to study. Not limited to AAM, who is the legislative candidate with the highest electability who succeeded in defeating 107 competitors from 13 different political parties in the 2019 Tulungagung District legislative election in the electoral district of Tulungagung II, which is the electoral district with the largest population in Tulungagung Regency, so this is a question mark about what kind of approach he applied to achieve this victory. Fundamentally, this research is a qualitative research, using in-depth interviews and document studies as data collection techniques, which are then validated using source triangulation techniques based on the Political Linkage Theory by Herbert Kistchelt as the analytical tool. As for the research, the results showed that there was a tendency for AAM to use clientelist linkage as a model for his political linkage with three forms of exchange, first, direct gifts in the form of money, clothing, food and other goods; second, special access in the form of benefits in public affairs through public institutions; and third, preferential access to jobs in the public/private sector regulated by public officials. In addition, this study found two